2017
DOI: 10.1159/000486328
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>MYC</i></b> Amplification in the Form of Ring Chromosomes 8 in Acute Myeloid Leukemia with t(11;16)(q13;p11.2)

Abstract: Oncogene amplification is uncommon in acute myeloid leukemia (AML). Cytogenetically, it is primarily found as double minute chromosomes (dmin) or homogeneously staining regions (hsr). A 62-year-old woman was admitted to our hospital because of anemia and thrombocytopenia. Her bone marrow was hypercellular with 78.6% myeloperoxidase- positive blasts. Some had micronuclei. The patient was diagnosed with AML M2 and remains in complete remission (CR) after induction therapy. G-banding at diagnosis showed 51,XX,t(1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In short, SKY was not able to identify the origin of dmin. In contrast, we previously demonstrated that dmin and ring chromosomes with MYC amplification in AML were completely labeled with the color of chromosome 8 by SKY [11,15]. Thus, it is possible that dmin contained chromosomal segments other than chromosome 8, suggesting that additional oncogenes originating from other chromosomes might be co-amplified with MYC.…”
Section: Discussionmentioning
confidence: 78%
“…In short, SKY was not able to identify the origin of dmin. In contrast, we previously demonstrated that dmin and ring chromosomes with MYC amplification in AML were completely labeled with the color of chromosome 8 by SKY [11,15]. Thus, it is possible that dmin contained chromosomal segments other than chromosome 8, suggesting that additional oncogenes originating from other chromosomes might be co-amplified with MYC.…”
Section: Discussionmentioning
confidence: 78%
“…3 b). To date, ring chromosome 8 has been reported in one prostate cancer patient [ 42 ] and four AML patients [ 43 46 ]. Previous studies have reported that the presence of ring chromosomes is associated with genomic instability and leads to numerous secondary chromosome rearrangements [ 47 ].…”
Section: Discussionmentioning
confidence: 99%